Biochemical investigation of steroids on metabolic sequelae and neurobiological effects (Texas Journal of Agriculture and Biological Sciences, 2022)
Steroids are hormone mediators that are synthesized commercially by humans and are used extensively in medicine. The cortex of the adrenal glands produces them naturally. They're used to treat steroid-responsive illnesses and dermatoses, which are a group of maladies. Corticosteroids are a two-edged sword: when used correctly and for a short period, they can provide significant benefit with a low incidence of side effects; however, the wrong dose and/or duration, as well as unmindful withdrawal after prolonged administration, can have disastrous consequences. Corticosteroids are employed in a variety of medical fields. In this review, we will discuss in detail all the metabolic sequelae and neurological effects of steroid use. Moreover, we are also going to discuss the adverse events associated with prolonged steroid use.